PENGARUH PEMBERIAN KONSENTRAT DAN ZEOLIT BERAMONIUM PADA RANSUM TERHADAP PERTAMBAHAN BOBOT TUBUH KAMBING BOERAWA - Olivia Eka Pratiwi; Erwanto .; Idalina Harris (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This study aimed to determine the effect of concentrate and amonium zeolite supplementation inration to the body weight gain of Boerawa goats. Fifteen Boerawa goats of 6—7 months old, withaverage initial body weight of 15,11 ± 4,44 kg/goat, were used in this experiment. This study usedRandomized Block Design with 3 treatments. The treatments were R0: ration of farmers, R1:ration of farmers 30% + concentrate 70%, and R2: R1 + amoniated zeolite 5% of ration dry matterof R1 with five replications. The water during this experiment was given ad libitum. The result ofthis study showed that the treatments of addition of concentrate without zeolite amoniated (R1)and addition of concentrate and zeolite amoniated R2 increased the body weight gain (P<0,05)compared with the treatments only addition of silage of cassava trunk and leaves (R0). However,the treatment of R2 showed the same result with R1 on the value of the body weight gain (P>0,05)of Boerawa goats. Besides, on the treatment R1 and R2 decreased the consumption of rude proteincompared with only R0 (P<0,01). However, on the treatment of R2 and R1 could increase theratio of protein efficiency which caused the increase of body weight heavier compared with R0 ofBoerawa goats (P<0,01).